(untitled) (International Journal of Communication Systems and Network Technologies, 2023)
This paper presents various medical image modalities employed for the prediction or detection of Breast carcinoma which is indeed a majorly occurring types of cancer in woman’s and also encapsulates the various techniques and approaches devised for the early screening and detection of breast cancer which either based on the conventional image processing and other advanced techniques. This paper tried to presents the various approaches in a simplified manner so that references can be taken to come up with the more advanced and robust methods for the detection and prediction of breast carcinoma (Cancer). All most, all of these approaches are based on the highly advanced technologies such as medical image processing and then techniques based on machine learning or deep learning. This paper is an attempt to illustrate and review some of the previously proposed approaches employed for the early detection of cancer of breast. These below mentioned prediction and detection techniques based on image processing and machine learning or deep learning provides an overview about the affordability, reliability and outcomes of each techniques.